Wajah-wajah pemimpin - Ab. Rahim Tahir, 1947- (Kuala Lumpur : Nasron Edar Marketing, 1996)
Politics and government in Malaysia, UMNO leaders; articles and interviews.
In Malay.
Keywords: United Malays National Organisation; Politicians -- Malaysia -- Interviews; Malaysia -- Politics and government